Revisiting the Mongolian Gerbil Model for Hepatitis E Virus by Reverse Genetics - Ling-Dong Xu; Fei Zhang; Chu Chen; Lei Peng; Wen-Ting Luo; Ruiai Chen; Pinglong Xu; Yao-Wei Huang (Microbiology Spectrum, 2022)
ABSTRACT Hepatitis E virus (HEV) is a major cause of acute viral hepatitis in humans. A convenient small mammalian model for basic research and antiviral testing is still greatly needed. Although a small rodent, the Mongolian gerbil, was reported to be susceptible to swine genotype-4 HEV infection, whether the previous results were reliable and consistent needs to be validated by using biologically pure HEV stocks or infectious RNA. In this study, we revisited this gerbil infection model for human HEV of genotype 1, 3, or 4 (G1, G3, or G4) by HEV reverse genetics. Gerbils inoculated intrahepatically with capped G3 HEV RNA transcripts or intraperitoneally with infectious G3 cloned HEV produced robust infection, as evidenced by presence of HEV in livers, spleens, and feces for up to 7 weeks post inoculation, seroconversion, and pathological liver lesions. Furthermore, the value of the gerbil model in antiviral testing and type I IFN in host defense was assessed. We demonstrated the effectiveness of peg-IFNα-2a and ribavirin in inhibiting HEV replication in gerbils. By treatment with two molecule inhibitors of TBK1, we also revealed a role of RIG-I like receptor-interferon regulatory factor 3 in host anti-HEV innate immune sensing in this in vivo model. Finally, susceptibility of G4 HEV was demonstrated in intrahepatically inoculated gerbils with infectious HEV RNA transcripts, whereas no evidence for G1 HEV susceptibility was found. The availability of the convenient gerbil model will greatly facilitate HEV-specific antiviral development and assess the mechanism of host immune response during HEV infection. IMPORTANCE HEV infects >20 million people annually, causing acute viral hepatitis as well as chronic hepatitis, neurological diseases, and pregnancy-associated high mortality, which require therapeutic intervention. The HEV antiviral research is largely limited by the lack of a convenient small animal model. Here we revisit the Mongolian gerbil model for three genotypes of human HEV by infectious HEV clones and recognized standards of experimental procedures. Fecal virus shedding, seroconversion, and pathological liver lesions could be detected in HEV-inoculated gerbils. We demonstrate the effectiveness and usefulness of this model in testing antiviral drugs, and in assessing the mechanism of host innate immune response upon HEV infection. This conventional rodent model will aid in future antiviral development and delineating mechanism of host immune response.